Lindtneria asiae-orientalis sp. nov. (Stephanosporaceae, Basidiomycota) from China based on morphological and molecular characters - Liu, Shi-Liang; Wu, Fang; He, Shuang-Hui (Phytotaxa, 2016)
Lindtneria asiae-orientalis sp. nov. is described and illustrated from Heilongjiang Province, northeastern China. This fungus is characterized by buff-yellow to orange-yellow poroid hymenophores, septate generative hyphae with or without clamps, and relatively small ellipsoid to broadly ellipsoid basidiospores (5.8–7 × 4.7–5.2 µm). Phylogenetic analyses based on three rDNA gene regions (ITS, nLSU and tef1-α) support Lindtneria asiae-orientalis as a distinct species within the family Stephanosporaceae.